2006
DOI: 10.1007/bf02820204
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of adolescents in rural Wardha

Abstract: Majority (53.8%) of the adolescents in this study area are thin and only 2.2% were overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
93
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 7 publications
14
93
3
1
Order By: Relevance
“…Undernutrition continues to be a major public health issue and a principal cause of ill-health condition 1,6 . The assessment of undernutrition bears great signifi cance in India; where a signifi cant proportion of the population is suffering from different grades of undernutrition [1][2][3]7,9,10,31 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Undernutrition continues to be a major public health issue and a principal cause of ill-health condition 1,6 . The assessment of undernutrition bears great signifi cance in India; where a signifi cant proportion of the population is suffering from different grades of undernutrition [1][2][3]7,9,10,31 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported the prevalence of stunting as a major nutritional problem among adolescents in India (Table 2). A high prevalence of stunting has been documented from Assam (51.90%) 8 , West Bengal (52.46%) 19 ,Wardha (50.70%) 6 , North Indian (37.20%) 40 and Karbi Anglong, Assam (51.20%) 29 . The National Nutrition Monitoring Bureau (NNMB) data showed that approximately 39.00%…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations